Mapping the digital transformation of AEC industry: Content analysis of digital public policy in China - Yumiao Yang; Sujuan Zhang; Yuanyuan Hua; Hua Wang (Developments in the Built Environment)
Governments arounds the world are relying on digital policies as a strategic tool to promote digital transformation objectives within the society. This study aims to investigate the evolutionary patterns and trends of China's digital public policies in the architectural, engineering, and construction (AEC) industry. Based on the policy instrument theory, the study develops a three-dimensional analysis framework of “policy topic - policy instrument - stakeholder” to analyze digital public policies. A total number of 56 policies, issued by the central government from 2001 to 2023 in China, were selected as data for content analysis. Using the Dynamic Topic Modeling, six main topics were identified from the texts: informatization development, smart construction, construction industrialization, BIM technology application, prefabricated building, and digital workforce. The results indicate that environment instruments have become central tools for the government to promote digital transformation. Stakeholders involved in digital public policies have remained relatively stable, with the government as the primary actor. The study sheds lights on the evolutionary path of digital public policies within the AEC industry in China. The findings provide a reference for digital policy improvement in the AEC industry and policy formulation in other developing countries for digital transformation.